USING A DATA BANK THAT AUTOMATES DIGITAL MAPS IN THE ArcGIS APPLICATION (American Journal of Technology and Applied Sciences, 2023)
Creation of digital maps and visualization of the socio-economic processes taking place in the world and its various regions on the basis of modern GIS (geo-information systems and technologies) is of great importance. Also, one of the important issues is the wide use of cartographic support methods in the study and analysis of the automated data bank. In this regard, among other things, in the study of agricultural, natural and socio-economic problems related to the development of the economy in the developed countries of the world, it is recommended to obtain reliable information about the territory with the help of electronic maps of the automated data bank. special attention is paid to the provision as the urgent tasks of modern mapping. To collect, store, analyze, process, evaluate and create a geodatabase using modern geo-information systems and technologies in world mapping in various fields, including the mapping of agricultural sectors, to create data visualization and electronic maps. great attention is being paid to conducting targeted scientific research aimed at the development of effective methods. This article talks about the important tasks of developing modern technologies of geo-information system and cartographic provision methods in improving the method of creating electronic maps describing the agricultural sector, taking into account socio-economic conditions.